Does perceived predation risk affect patterns of extra‐pair paternity? A field experiment in a passerine bird. (23rd February 2018) - Abbey‐Lee, Robin N.; Araya‐Ajoy, Yimen G.; Mouchet, Alexia; Moiron, Maria; Stuber, Erica F.; Kempenaers, Bart; Dingemanse, Niels J.
Abstract: Non‐consumptive predator effects have been shown to influence a wide range of behavioural, life history and morphological traits. Extra‐pair reproduction is widespread among socially monogamous birds and may incur predation costs. Consequently, altered rates of extra‐pair reproduction are expected in circumstances characterized by increased adult perceived predation risk. In addition, extra‐pair reproduction is expected to be most affected for birds with phenotypes that generally increase predation risk (such as more active individuals). In two consecutive years, perceived predation risk was manipulated for great tits Parus major breeding in 12 nest‐box plots by broadcasting sounds of their main predator (European sparrowhawk Accipiter nisus ; six plots). As a control treatment, sounds of a sympatric, avian non‐predator species were broadcast (Eurasian blackbird Turdus merula ; six plots). Levels of extra‐pair paternity did not differ between plots with different predation risk treatments. Males that moved more in a novel environment (more active or "faster exploring") tended to have offspring with fewer partners, but this effect did not vary with predation risk treatment. From an adaptive viewpoint, predation costs associated with extra‐pair reproduction may be small and may not outweigh the benefits of extra‐pair behaviour. Research on a broader range of taxa with different mating strategies is now needed to confirm the generality of our findings. A plain language summary is available for this article. Abstract : Plain Language Summary